Impulse Buying in the TikTok Shop Era: A Literature Review on the Role of Positive Emotions, Live Streaming, and Price Discounts - Yunita Fitri Wahyunintyas (Yayasan Ilomata, 2026)
Impulse buying has become a dominant consumer behavior in the digital era, especially with the rise of social commerce platforms such as TikTok Shop. Unlike traditional e-commerce, TikTok Shop integrates entertainment, live interaction, and real-time promotions to stimulate spontaneous purchase decisions. This conceptual literature review aims to examine the role of positive emotions, live streaming, and price discounts as key factors driving impulse buying in the context of TikTok Shop. By referring to the Stimulus-Organism-Response (S-O-R) framework, this study explores how emotional, interactive, and economic stimuli shape consumer behavior in a dynamic digital environment. The study synthesizes theories of affective marketing, social interaction, and behavioral economics to build an integrative perspective on impulse buying in the era of social commerce. Findings suggest that impulse buying is not simply an irrational act, but the result of systematic experience design. Future research directions are proposed, including experimental and mixed-method approaches to deepen the understanding of digital impulse consumption.